UPAYA GURU DALAM MENINGKATKAN RASA PERCAYA DIRI SISWA PADA PEMBELAJARAN BAHASA ARAB DI KELAS X MAN 2 MUARO JAMBI - Ike Dwi Saputri; Helty; Salman Jufri; Mar’atun Sholiha; K. A. Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the efforts of Arabic language teachers in increasing students’ self-confidence in Arabic learning in class X of MAN 2 Muaro Jambi and to identify the obstacles faced by teachers in the learning process. This research used a qualitative approach with a descriptive method. The research was conducted at MAN 2 Muaro Jambi from July 15 to August 15, 2025. Data were collected through observation, interviews, and documentation. The participants in this study consisted of an Arabic language teacher, the vice principal of curriculum, and class X students of MAN 2 Muaro Jambi. The results showed that the teacher’s efforts to increase students’ self-confidence were carried out through emotional approaches, motivation, appreciation, repeated explanations, open communication, and enjoyable learning methods. The teacher also created an inclusive classroom atmosphere by accepting students’ questions and opinions and giving opportunities for students to appear in front of the class. Supporting factors in increasing students’ self-confidence included the teacher’s emotional approach, appropriate learning methods, and a pleasant learning atmosphere. Meanwhile, the inhibiting factors included students’ anxiety when speaking, lack of mastery of the material, low concentration during learning, peer influence, and limited learning media such as LCD projectors. Therefore, Arabic language teachers need to continuously develop creative strategies to help students become more confident in learning Arabic.